Antimoulting Activity of Eremanthus erythropappus (DC.) MacLeisch - Barbosa, Danielle Castilho; Silvério, Marcelo Silva; Velozo, Leosvaldo Salazar Marques; Kaplan, Maria Auxiliadora Coelho; Cabral, Marise Maleck Oliveira (EntomoBrasilis, 2012)
Extracts and secondary metabolites from plants can act as feeding deterrents, toxic agents or developmental disruptors in insects. In this study, the experimental milkweed bug Oncopeltus fasciatus (Dallas), (Hemiptera) was used to evaluate the activities of crude ethanol extract and fractions, obtained from flowers or stems of Eremanthus erythropappus (DC.) MacLeisch (Asteraceae), on its mortality and development. Butanol fraction from ethanol extract showed toxicity against nymphs of O. fasciatus as well as growth inhibition activity. The results imply that E. erythropappus butanol fraction has active substances on this insect growth development physiology. Atividade Antimuda de Eremanthus erythropappus (DC.) MacLeisch Resumo. Os extratos e metabólitos secundários de plantas podem agir como agentes tóxicos e inibidores do da alimentação e do desenvolvimento em insetos. Neste estudo foi utilizado Oncopeltus fasciatus (Dallas) (Hemiptera) como modelo experimental a fim de avaliar as atividades do extrato etanólico bruto e frações obtidos das flores ou caules de Eremanthus erythropappus (DC.) MacLeisch (Asteraceae), na mortalidade e sobre o desenvolvimento do inseto. A fração butanólica obtida do extrato etanólico mostrou toxidade sobre as ninfas de O. fasciatus, bem como atividade de inibição do crescimento. Os resultados sugerem que a fração butanólica de E. erythropappus possui substâncias ativas sobre a fisiologia, crescimento e desenvolvimento de insetos.